Pyrites of west flank of Sukholozhskoe gold ore field (Lensk ore district) - Anatoliy Yakovlevich Pshenichkin; Roman Yurievich Gavrilov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
The relevance of the study is caused by the need to introduce new complex methods for predicting gold ore objects into the practice of geological exploration. The aim of the research is to obtain information on crystal morphology, thermos-emf, chemical composition and impurity elements of pyrite from the ore zone of the western flank of the Sukholozhsky ore field. Methods: crystal morphology, thermal electromotive force, X-ray spectral analysis, statistical processing of geochemical data on samples of pyrite crystals taken from the ore zone of the western flank of the Sukholozhsky ore field. Results. It was determined that the studied pyrite crystals are found most often in the form of cubes. Often on crystals there is a poorly developed face {210}. Pyrite is characterized exclusively by a hole type conductivity with a spread of thermal electromotive force values from 27 to 83 mV and close average values within the range of 58,4...67,0 mV. The chemical composition of pyrite crystals differs from their stoichiometric formula, which indicates the occurrence of isomorphic impurities (As) in the mineral structure. X-ray spectral analysis revealed the elements that are constantly present in pyrite: Co, Ni, Cu, Zn, As, Pb. The presence of impurity elements in pyrites, typical for the ores of the Sukhoy Log deposit, and especially As, indicates pyrite synore formation during hydrothermal-metasomatic process and its possible entry in the form of isomorphic impurities into mineral structure. Pyrrhotite, chalcopyrite, sphalerite, galena, arsenopyrite, thorianite are defined as mechanical impurities in pyrite. Based on the study of crystallomorphology, thermal electromotive force, chemical composition of pyrites, and distribution of impurity elements in them, a conclusion was made on the upper ore level of the ore zone erosional section in the western flank of the Sukholozhsky ore field.